The Effect Of Giving Soy Flour And Lunges Exercises On The Ability Of Kick Speed In Front Of Pencak Silat Athletes Of The Center For Education And Sports Training (PPLP) Of West Sumatra - Rully Effendi; Wilda Welis (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This study aims to find out the effect of soy milk flour and lunges training on the ability of kick speed in front of pencak silat athletes of the Center for Education and Sports Training (PPLP) of West Sumatra. This study was conducted from June until October 2021. The type of this research was a pseudo experiment with the research population was all pencak silat athletes from sports education and training center (PPLP) students of West Sumatra, which amounted to 14 people. The sample of these 14 people was taken based on the total sampling techniques. The instrument in the study used a test of the forward kick speed ability to measure the front kick. The data analysis technique was done by testing one way anava with a significant level = 0.05. From the analysis of data, the researcher found the results;  ̄x Pree Test is 15.36, Central Data is 18.86, and Post Test is 23.14. The results of statistical tests have an effect on the provision of soy milk flour and lunges training on the ability of kicking in front of pencak silat athletes of the Center for Education and Sports Training (PPLP) of West Sumatra, with a α < of 0.05.